2013
DOI: 10.3748/wjg.v19.i46.8714
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal stem cell marker LGR5 expression during gastric carcinogenesis

Abstract: Enhanced LGR5 is related to progressive dedifferentiation and metastasis of gastric cancer, indicating the potential of this receptor as an early diagnostic and prognostic biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
2
31
1
Order By: Relevance
“…It found that patients with gastric cancer and H pylori infection had an expanded pool of LGR5 + stem cells in the antrum, and higher amounts of DNA oxidative damage in these stem cells 111 . Several other studies have confirmed that levels of LGR5 mRNA and protein are increased in stomach tissues from patients with gastric cancer 112, 113 . Higher levels of LGR5 may be a marker of poor prognosis for patients with gastric cancer 114 .…”
Section: Effects On Gastric Stem Cellsmentioning
confidence: 75%
“…It found that patients with gastric cancer and H pylori infection had an expanded pool of LGR5 + stem cells in the antrum, and higher amounts of DNA oxidative damage in these stem cells 111 . Several other studies have confirmed that levels of LGR5 mRNA and protein are increased in stomach tissues from patients with gastric cancer 112, 113 . Higher levels of LGR5 may be a marker of poor prognosis for patients with gastric cancer 114 .…”
Section: Effects On Gastric Stem Cellsmentioning
confidence: 75%
“…There was no correlation between Lgr5 expression and the clinicopathological variables examined in our study. In contrast, previous studies have identified a positive correlation between Lgr5 expression and depth of tumor invasion, lymph node metastasis, and distant metastasis in invasive gastric carcinoma . Another study has reported a positive association between Lgr5 expression and age, tumor differentiation, Lauren type, and TNM stage .…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, previous studies have identified a positive correlation between Lgr5 expression and depth of tumor invasion, lymph node metastasis, and distant metastasis in invasive gastric carcinoma. 17,18 Another study has reported a positive association between Lgr5 expression and age, tumor differentiation, Lauren type, and TNM stage. 17 Furthermore, recent investigations have demonstrated that patients expressing Lgr5 have a worse prognosis than those that do not.…”
Section: Discussionmentioning
confidence: 99%
“…There is clinical evidence for a role of Lgr5+ cells in the carcinogenesis of GC [29][30][31][32]. However, most of thise evidence come from the analyses on the clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…In stomach, Lgr5+ stem cells drive self-renewal and can build long-lived gastric units in vitro [28]. Helicobacter pylori infection has been associated with the increases in Lgr5-positive cells in the stomach of patients with gastric cancer, and been hypothesized to relate to gastric carcinogenesis, based on clinical data [29][30][31][32]. However, the role of Lgr5-positive cells in GC has not been extensively tested for their CSC characteristics in vitro using molecular biological methods.…”
Section: Introductionmentioning
confidence: 99%